Insights into the evolutionary relationships within the Delphininae, with focus on the genus Delphinus : a multi-locus, multi-disciplinary approach - Amaral, Ana Rita Gabirro da Silva Teixeira do, 1981- (2011)
Tese de doutoramento, Biologia (Biologia Evolutiva), Universidade de Lisboa, Faculdade de Ciências, 2011